The gatekeeper's dilemma: Political selection or team effort - Jon H. Fiva; Federica Izzo; Janne Tukiainen (Aboa Centre for Economics (ACE), 2024)
Political parties play a crucial gatekeeping role in elections, including controlling electoral resources, candidate recruitment, and electoral list compositions. In making these strategic choices, parties aim to encourage candidates to invest in the campaign, while also trying to secure advantages for their preferred candidates. We study how parties navigate this trade-off using a specific feature of the Norwegian local electoral system in which parties can give advantaged positions to some candidates in an otherwise open list. Our theory reveals that parties' ex-ante electoral strength impacts their strategic decisions. Notably, the trade-off is weaker for more popular parties, allowing them to facilitate the election of their preferred candidates without compromising the party's overall performance. We show empirically that the moral hazard concern is real, and that larger parties are indeed more likely to use their power to make some candidates safe. The advantage of large parties extends further: safeguarding specific candidates enables parties to achieve disproportionately favorable outcomes in post-electoral bargaining. These findings reveal new insights for political representations, policy outcomes, and intra-party dynamics more broadly.
Keywords: C21; D72; 330; Intra-party politics; flexible party lists; campaigning; moral hazard; seniority norms; bargaining